ANALISIS PENGAWASAN UNIT APRON MOVEMENT CONTROL (AMC) TERHADAP AKTIVITAS MARSHALLER DI APRON BANDAR UDARA H. ASAN SAMPIT - Rivan Nuriansyah (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2024)
The prevention of accidents between aircraft and obstructing objects on the apron is controlled by a unit, namely Apron Movement Control. This unit also plays a role in regulating aircraft maneuvers, regulating the movement of vehicles or facilities on the apron, providing information services for aviators and related units if there is a special need. This unit must ensure the security, safety, and smooth operation of flights, especially on the apron. The authors used qualitative data types that focused on the Apron Movement Control (AMC) Unit and marshaller in addition to other information relevant to this study. Primary and secondary data are the data sources for this study. In this research, the data analysis technique used is descriptive analysis. The data obtained from observations, interviews, and documentation will be compiled with a narrative pattern that presents information about the situation being studied and the phenomenon in the field. The results of this study show that the process of supervising marshaller activities when guiding the maneuvering aircraft to the parking lot that has been determined by the AMC is running well. However, a marshaller had violated several safety regulations. The Apron Movement Control (AMC) unit is doing a good job, but they need to be more resolute and bold to prevent violations, such as imposing sanctions that include withholding the Airport Pass or revocation to ensure safe and comfortable flight operations.